The effect of utilizing package books on increasing understanding of virtual self-learning of social studies subjects - Ramadhanti, Maskonah (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
This study aims to determine the effect of using textbooks on improving the understanding of social studies subjects during the pandemic in 7th grade students of SMP Pasundan 6 Bandung. The learning system that was originally conventional became virtual learning that made learning using digital. This study uses quantitative methods with questionnaires and literature data collection techniques. The population in this study were students in grades 7A, 7B, and 7C with a total sample of 66 people. The results of the study showed that 7th graders at Pasundan 6 Bandung Junior High School experienced an increase in understanding of self-study material for social studies subjects virtually during the Covid-19 pandemic. The effect of using textbooks simultaneously on students’ self-study understanding of social studies subjects during the COVID-19 pandemic virtually for 7th graders at SMP Pasundan 6 Bandung based on the table above is around 60.5%, the rest is influenced by other variables.